PENGARUH MOTIVASI KERJA, TEAM WORK DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA PEGAWAI KESEHATAN DI BIDDOKES POLDA SULTRA - Nanny Zaitun; Aidin Hudani Awasinombu; Endro Sukotjo; Hastuti Hastuti; La Ode Bahana Adam; Nuryamin Budi (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this research is to know the influence of work motivation, Team Work and Interpersonal communication towards Kinerjai Health officer in the POLDA SULTRA Biddokes. This research approach is to use explanatory research. Data collection is done Cross Sectional Study by using instrument in the form of poll. The population of this study was all the officers of the POLDA Sultra Biddokes with a total of 196 people. The samples in this study numbered 66 people based on the sample formula. The analysis equipment used is regression analysis.The results showed that work motivation, Team Work and Interpersonal communication have positive and significant effect on improving the performance of the Biddokkes POLICE officer Sultra. Based on test results of multiple linear regression analyses, regression coefficient, correlation coefficient, coefficient of determination, and regression partial (t). Thus it can be concluded that the work motivation, Teamwork and Interpersonal communication contributed positively and significantly to the performance of POLICE Biddokkes Sultra.